Geriatric assessment among older adults receiving intensive therapy for acute myeloid leukemia: Report of CALGB 361006 (Alliance). Issue 1 (January 2020) - Klepin, Heidi D.; Ritchie, Ellen; Major-Elechi, Brittny; Le-Rademacher, Jennifer; Seisler, Drew; Storrick, Libby; Sanford, Ben L.; Marcucci, Guido; Zhao, Weiqiang; Geyer, Susan A.; Ballman, Karla V.; Powell, Bayard L.; et al.
Abstract: Objective: To demonstrate feasibility of performing geriatric assessment (GA) in the National Clinical Trials Network (NCTN) and to explore the utility of GA to characterize treatment tolerance. Materials and methods: We conducted a multisite companion study (CALGB 361006) to CALGB 11001, a phase 2 trial of adults ≥60 years old with newly diagnosed FLT3- mutated AML, testing the efficacy of adding sorafenib to intensive chemotherapy. On 361006, a GA was administered prior to induction and prior to post-remission therapy. The GA is divided into items requiring administration by a health care professional (HCP) and patient self-administered questionnaires. Feasibility outcomes were recruitment rate, time to GA completion, difficulty with GA administration, percent of patients requiring assistance, and satisfaction. Change in GA measures pre- and post-induction were compared using Wilcoxon signed rank test and McNemar's tests. Results: The recruitment rate was 80% (N = 43, median age 68 years). Median completion time of the GA was 30 min; (10 and 21 min for HCP and patients, respectively). HCP reported no difficulty completing assessments (100%). Most patients completed questionnaires without assistance (77%), and were satisfied with the length (89%). Self-reported physical function, mental health, social activity and nutritional parameters worsened after induction. Conclusion: GA is feasible to administer in the setting of intensive induction for older adults with AML in the NCTN and provides evidence of the impact of induction therapy on physical and emotional health.